Chewing function, general health and the dentition of older Australian men: The Concord Health and Ageing in Men Project. Issue 2 (20th November 2018) - Wright, Fredrick A. C.; Law, Garry G.; Milledge, Kate L.; Chu, Steven K.‐Y.; Hsu, Benjumin; Valdez, Eduardo; Naganathan, Vasi; Hirani, Vasant; Blyth, Fiona M.; LeCouteur, David G.; Waite, Louise M.; Handelsman, David J.; et al.
Abstract: Objectives: To describe the associations between chewing function with oral health and certain general health characteristics, in a population of community‐dwelling older Australian men. Methods: Analysis of data obtained from a cross‐sectional analysis of the 4th wave of the Concord Health and Ageing in Men Project cohort of 614 participants, 524 whom were dentate, aged 78 years and over. Their chewing capacity was assessed using three main indicators: capacity to chew eleven food items ranging from boiled eggs through to fresh carrots and nuts; discomfort when eating; and interruption of meals. Associations with chewing were tested for dentate vs edentate participants, numbers of teeth present, active dental disease and key general health conditions such as disabilities, comorbidities and cognitive status. Log binomial regression models adjusted for age, country of birth, income, education and marital status. Prevalence ratios and 95% confidence intervals were estimated. Results: Twenty‐one per cent of participants could not eat hard foods, while 23.1% reported discomfort when eating, and 8.8% reported interrupted meals when eating. There was a threefold difference in the capacity of dentate men to chew firm meat over that of edentulous men (95% CI, 2.0‐4.9); a 2.5 times greater likelihood of edentate men reporting discomfort when eating (95% CI: 1.5‐4.3); and 1.9 times greater likelihood of edentate participants reporting having meals interrupted (95% CI: 1.4‐2.6). Chewing/eating difficulties were associated with both dental status (number of teeth, active dental caries) and self‐rated dental health. Fewer than 20 teeth and the presence of active coronal or root decay were associated with more discomfort when eating. General health conditions associated with chewing function included disability, physical activity, comorbidities, cognitive status and depression. Older men's self‐rated oral health and general health perceptions were also associated with aspects of chewing function. Poorer self‐reported oral health was associated with inability to eat hard foods (95% CI: 1.3‐2.7) and with discomfort when eating (95% CI: 2.6‐5.1), while poorer self‐reported general health was associated with discomfort when eating (95% CI: 1.2‐2.2). Conclusions: Falling rates of edentulism may lead to improved chewing and eating function in older men. Maintaining 20 or more natural teeth, and preventing active coronal and root caries should enhance chewing function and promote self‐reported health and oral health. Lower capacity to chew hard foods and a higher reporting of discomfort when eating is associated with co‐morbidity in older Australian men.